Transformasi Pembelajaran dengan Teknologi Digital - Juniarti, Aristia; Sulastika, Rika (Journal of Innovation in Teaching and Instructional Media, 2025)
This research aims to explore and analyze the transformation of learning through digital technology based on a comprehensive literature review. The main focus of this study is to identify the impacts, challenges, and opportunities presented by the use of digital technology in education, especially in the context of distance and hybrid learning. The method used is a literature review that includes scientific articles, journals, and relevant research reports from 2021 to 2024. The analysis was carried out by categorizing the research results into main themes such as pedagogical innovation, technological adaptation, and changes in the roles of educators and students. The results show that the application of digital technology has changed the way learning is carried out, from flexibility of time and place, to increased student participation and collaboration. However, there are significant challenges in terms of infrastructure readiness, digital competence, and speed. The novelty of this research lies in a holistic approach that combines various perspectives on learning transformation from different disciplines, while offering a roadmap for the development of more effective technology-based learning policies and practices. The contribution of this research provides in-depth insights for decision-makers, educators, and researchers to understand how digital technology can be optimally utilized in the learning process. In addition, this study contributes to the development of technology-based educational theories and provides strategic recommendations to increase the effectiveness and inclusivity of learning in the digital era.